PERFORMANCE OF TRANSPLANTED SCENTED RICE (ORYZA SATIVA L.) UNDER SRI BASED CULTIVATION PRACTICES; A SUSTAINABLE METHOD FOR CROP PRODUCTION - THAWAIT, DAMINI; K. PATEL, AMIT; KAR, SAMAPTIKA; SHARMA , MANISH KUMAR; MAYUR R.; MESHRAM (The Bioscan, 2014)
The experiment was carried out at Raipur during season of 2012 to find out the performance of transplanted scented rice under different planting geometries and seedling densities. The treatment (T2) i.e. planting of 2-3 seedlings hill-1 transplanted in the spacing of 25 cm x 25 cm recorded significantly highest i.e. Plant height (129.64cm), number of tillers (15.70 tillers hill-1), dry matter accumulation (102.65 g hill-1) and yield attributing characters along with highest grain yield i.e. 38.20 q/ha and straw yield ( 77.91 q/ha). Therefore its adoption protects the ecosystem as well as increasing production also.